2007
DOI: 10.1111/j.1600-0846.2007.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin lesion classification using relative color features

Abstract: Background/purpose-Clinically, it is difficult to differentiate the early stage of malignant melanoma and certain benign skin lesions due to similarity in appearance. Our research uses image analysis of clinical skin images and relative color-based pattern recognition techniques to enhance the images and improve differentiation of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…[21][22][23][24][25] To our best knowledge, no attempt was done for extraction of blood oxygenation using PCA from RGB or multispectral images or for comparison of PCA to reconstruction results. The reconstruction results of four healthy volunteers undergoing occlusion of the upper arm and imaged at the forearm ͑Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25] To our best knowledge, no attempt was done for extraction of blood oxygenation using PCA from RGB or multispectral images or for comparison of PCA to reconstruction results. The reconstruction results of four healthy volunteers undergoing occlusion of the upper arm and imaged at the forearm ͑Fig.…”
Section: Discussionmentioning
confidence: 99%
“…21 Applied to RGB images, PCA was used on relative color features for unsupervised lesion classification. [22][23][24] When imaging the skin in the visible light range, the dominant absorbing materials are blood and melanin and should therefore explain most of the variance in multispectral data. Previous work by Tsumura et al 25 showed that skin color in digital RGB images can be described by attributing melanin and blood to the first two principal components.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of efforts have been dedicated in solving this challenging problem. Early investigations are achieved to apply low-level hand-crafted features to distinguish melanomas from non-melanoma skin lesions, including, color [5],shape [6] and texture [7], [8]. Some of the researchers are undertaken to employ feature selection algorithms to select proper features and utilized combinations of these low-level features to improve the recognition performance [9], [10].…”
Section: Literature Surveymentioning
confidence: 99%
“…This improved spectral resolution allows for better tissue discrimination, however this is hampered by the presence of large illumination changed across the image. As lesion classification methods [3] rely on many features that can be observed on a lesion, such as color and fine structures, they are quite sensitive to illumination changes. Our motivation is to exploit the additional information of multispectral imaging, in order to compensate for such illumination changes, while preserving both morphological and colorimetric (spectral) features of the lesions.…”
Section: Introductionmentioning
confidence: 99%